Виявлення безпілотних літальних апаратів засобами відеоспостереження - Логвінов, О. С. (ХНУРЕ, 2021)
One of the directions in the detection of unmanned aerial vehicles (UAV) is visual observations. In systems for detecting UAVs from video images, video cameras operating in the visible and infrared ranges are used, powerful video analytic software for detecting, tracking, and classifying UAVs in real-time. Today, the urgent tasks are the design of UAV location detection systems, development of measures, and tools to reduce emerging threats.
Keywords: БЛА; відеоспостереження; БПЛА